Usulan Perbaikan Kerja untuk Meningkatkan Keselamatan Kerja di PD. Jaya Rasa menggunakan metode HIRADC - Cahyadi, Ujang; Nur Ajhar, Alfi; Taptajani, Dedi Sa'dudin (Jurnal Kalibrasi, 2025)
Company safety is greatly affected by work accidents. PD. Jaya Rasa is an industry in the food sector that produces macaroni where there are potential hazards that can cause losses to the company starting from the production process area which is the main cause of many accidents at work including lan.Therefore, the purpose of this study is to determine the potential hazards that exist in the production area of PD. Jaya Rasa and determine the level of risk of these hazards and propose recommendations for work improvements to improve work safety. The method used is the hazard identification risk assessment and determining control method which serves to identify potential hazards, assess the level of risk and provide recommendations for hazard control. Hazard identification is carried out through field observations and interviews with company owners and employees in the production process area. While the risk assessment is carried out through the stages of hazard identification and data from how often the accident occurs and the impact of the accident which will be calculated using the scale set by AS/NZS: 2004.The results obtained there are 22 levels of hazard risk including 1 extreme risk (4%), 4High risk (18%), 7 Medium risk (31%) and 10 low risk(45%). Where in each existing work activity of the 5 work activities that have the highest and extreme risk level, namely in the work activities of frying, seasoning and gluing macaroni. Then based on the hierarchy of k3 control, the resulting controls for improvement in PD. Jaya rasa are elimination, substitution, administrative design and personal protective equipment.